Examination of Stochastic and Deterministic Perturbations in Reactor Physics. Issue 6 (18th September 2016) - Kis, Daniel P.; Szatmary, Zoltan
ABSTRACT: The general solution of the perturbed diffusion equation in case of localized random perturbation is discussed in details. The auto-covariance function of the flux perturbation and the reaction rate have been calculated by Green-function technique, and the algorithm is tested with some special analytic solutions. The reactivity and the variance of reactivity in cases of different perturbations has been determined numerically.